Safety of marine transport marine navigation and safety of sea transportation - Weintrit, Adam,eeditor; Neumann, Tomasz,eeditor (CRC Press/Balkema, 2015)
Providing high-quality, scholarly research, addressing development, application and implications, in the field of maritime education, maritime safety management, maritime policy sciences, maritime industries, marine environment and energy technology. Contents include electronics, astronomy, mathematics, cartography, command and control, psychology, operational research, risk analysis, theoretical physics, operation in hostile environments, instrumentation, ergonomics, financial planning and law. Further, logistics, transport and mobility are addressed n this volume